Etnomatematika pada Tradisi Begalan Banyumasan - Najma Aufa Khansa; Raekha Azka (Pusat Studi Pengembangan Pembelajaran Matematika, 2024)
This research reveals the importance of ethnomathematics in mathematics education, particularly in the context of the Begalan Banyumasan tradition. Begalan Banyumasan is a traditional performance that contains symbolic meanings in the tools used, such as wangkring, ian, ilir, kukusan, cowek, and muthu. In this tradition, each tool has a profound meaning that can be related to mathematical concepts, such as cylindrical and conical shapes, square and rectangular shapes, and circles. The research method used is qualitative with an ethnographic approach. Data were collected through reviews of articles, journals, and webpages relevant to the Begalan Banyumasan tradition. The results show that the Begalan Banyumasan tradition can be used as a means to understand mathematical concepts in daily life through tools that have symbolic meanings.